2023
DOI: 10.14411/fp.2023.008
|View full text |Cite
|
Sign up to set email alerts
|

First report of Spirometra (Eucestoda; Diphyllobothriidae) naturally occurring in a fish host

Abstract: Spirometra Faust, Campbell et Kellogg, 1929 is a genus of cestodes belonging to the family Diphyllobothriidae. To date, amphibians, reptiles, and mammals are known second intermediate hosts of these parasites; humans can also be infected (the zoonotic disease is known as sparganosis or spirometrosis). Although the number of phylogenetic studies on Spirometra spp. has increased worldwide in recent years, there are few in South America. Specifically in Uruguay, molecular studies have shown that tapeworms of S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This complex 1 consists of specimens of various South American carnivores (adults) and plerocercoids of reptiles and humans, including the enigmatic Sparganum proliferum ( Arrabal et al, 2020 ). Vettorazzi et al (2023) have also indicated the rivulid killifish Austrolebias charrua as paratenic host of this tapeworm, which is the first report of Spirometra plerocercoids in fish.…”
Section: Survey Of Spirometra Speciesmentioning
confidence: 86%
See 4 more Smart Citations
“…This complex 1 consists of specimens of various South American carnivores (adults) and plerocercoids of reptiles and humans, including the enigmatic Sparganum proliferum ( Arrabal et al, 2020 ). Vettorazzi et al (2023) have also indicated the rivulid killifish Austrolebias charrua as paratenic host of this tapeworm, which is the first report of Spirometra plerocercoids in fish.…”
Section: Survey Of Spirometra Speciesmentioning
confidence: 86%
“…Small aquarium fish, catfish ( Ameiurus melas [Rafinesque], Cnidoglanis macrocephalus [Valenciennes], Silurus glanis L.), mosquitofish ( Gambusia affinis Baird et Girard), goldfish ( Carassius auratus [L.]) and rainbow trout ( Oncorhynchus mykiss [Walbaum]) were used unsuccessfully in laboratory experiments ( Joyeux et al, 1934 ; Mueller, 1960 ; Odening and Bockhardt, 1982 ; Stephanson, 1985 ). However, Vettorazzi et al (2023) reported a natural infection of the killifish Austrolebias charrua Costa et Cheffe (Cyprinodontiformes: Rivulidae) in Uruguay. The prevalence of infection was high (up to 58%), but the actual role of killifish in the life cycle of Spirometra tapeworms is not known.…”
Section: Life Cycle and Host Associationsmentioning
confidence: 99%
See 3 more Smart Citations